2020
DOI: 10.1002/ccd.29263
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular lithotripsy in calcified‐coronary lesions: A real‐world observational, European multicenter study

Abstract: Background The recently introduced intravascular lithotripsy (IVL) appears promising and relatively safer than conventional approaches when dealing with calcified lesions. Although there are published reports on this novel technology, data from the real world are limited. In this study, we aim to report on the experience of IVL from a real‐world population derived from six European centers that undertake high‐volume complex coronary interventions. Methods and results We enrolled all patients treated with IVL b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 37 publications
4
23
1
Order By: Relevance
“…Published real-world data from the several registries worldwide including the SING-IVL registry, 5 a European Multicentre registry 6 and a German multicentre registry by Aksoy et al , 7 all demonstrated similarly low complication rates. In the latter registry, there was a 9% balloon rupture rate.…”
Section: Discussionmentioning
confidence: 90%
“…Published real-world data from the several registries worldwide including the SING-IVL registry, 5 a European Multicentre registry 6 and a German multicentre registry by Aksoy et al , 7 all demonstrated similarly low complication rates. In the latter registry, there was a 9% balloon rupture rate.…”
Section: Discussionmentioning
confidence: 90%
“…In the study presented by Aziz et al MACE was 2.6%, including two cardiac deaths (1%), one TVMI (0.5%) and three cases of TLR (1.5%). 14 The mean follow-up was 222 days.…”
Section: Discussionmentioning
confidence: 99%
“…Several technological developments have been introduced to aid in the treatment of severely calcified coronary lesions. Recently, intravascular lithotripsy (IVL), a balloon-based calcium-modifying technique, has been introduced as a promising strategy, which is simple to use, with a high rate of procedural success and a low rate of complications (3)(4)(5)(6). Nevertheless, data regarding IVL use in distinctive anatomical settings and different clinical indications are scarce and longterm data using this therapeutic approach are lacking.…”
Section: Introductionmentioning
confidence: 99%